THE PRINCIPLES OF MODERN ARCHITECTURAL DESIGN AS OBSERVED IN PARAHYANGAN CATHOLIC UNIVERSITY’S POSTGRADUATE STUDIES BUILDING - Bryan Nurman Zachrie ; Caecilia Wijayaputri (Riset Arsitektur (RISA), 2018)
Abstract - The post-Independence era saw the beginning of the development of modern architecture in Indonesia. In this particular era the profession of architect emerged as a requirement that eventually also turned into one of the fields that played a role in the development of Indonesian architecture. As one of the first architects, Mohammad Soesilo joined in participating in drawing up the main principles of architectural design valid for that era, a theorem that can be said to be influential to this day, serving as a set of general guidelines. The lack of data available on the dawn of architectural development has created a certain vagueness concerning these principles. In the post-Independence era, Indonesian architects were still strongly influenced by the principles of design being developed, that is to say those governing modern architecture. The purpose of this research is to deepen our insight into into the various principles of architectural design in the post-Independence era to establish how big the influence has been of the principles governing modern architecture that became the guidelines for designs made by Indonesian architects in those days, in order to be able to determine their impact on the design of architectural works in Indonesia itself. This research has been conducted by examining one of the buildings designed by Mohammad Soesilo, namely Parahyangan Catholic University’s Post-graduate Studies Building. The focus of research revolves around the question whether this building can be classified as one designed with the principles of modern architecture in mind because the design of its physical shape was influenced by the seven variables using the terminology of modern architecture. These seven variables have influenced the attainment of function, expression, and technology in Parahyangan Catholic University’s Post-graduate Studies Building as one that has been well designed. Keywords : Architectural principles, Principles of Modern Architecture, Post-Independence Architecture